Bilateral chylothorax after blunt thoracic trauma: a case report - Serin-Ezer, Semire; Oğuzkurt, Pelin; Ince, Emine; Hiçsönmez, Akgün (The Turkish Journal of Pediatrics, 2009)
Traumatic chylothorax other than iatrogenic thoracic duct injury is extremely rare in children. Chylothorax can cause cardiopulmonary abnormalities and significant nutritional, metabolic and immunologic consequences. The management of chylothorax ranges from conservative treatment to surgical intervention. We present a four-year-old boy who presented with respiratory difficulty due to multiple rib fractures and bilateral chylothorax, which developed after a blunt chest trauma. The patient was successfully treated through a conservative approach with total parenteral nutrition, nothing by mouth, and bilateral chest tube drainage. The nature of pleural effusion developed following a blunt thoracic trauma is important in the management of trauma patients.